Bacteriophage-Derived Double-Stranded RNA Exerts Anti-SARS-CoV-2 Activity In Vitro and in Golden Syrian Hamsters In Vivo - Kristine Vaivode; Irina Verhovcova; Dace Skrastina; Ramona Petrovska; Madara Kreismane; Daira Lapse; Zane Kalnina; Kristine Salmina; Diana Rubene; Dace Pjanova (MDPI AG, 2022)
Bacteriophage-derived dsRNA, known as Larifan, is a nationally well-known broad-spectrum antiviral medication. This study aimed to ascertain the antiviral activity of Larifan against the novel SARS-CoV-2 virus. Larifan's effect against SARS-CoV-2 in vitro was measured in human lung adenocarcinoma (Calu3) and primary human small airway epithelial cells (HSAEC), and in vivo in the SARS-CoV-2 infection model in golden Syrian hamsters. Larifan inhibited SARS-CoV-2 replication both in vitro and in vivo. Viral RNA copy numbers and titer of infectious virus in the supernatant of Calu3 cells dropped significantly: p = 0.0296 and p = 0.0286, respectively. A reduction in viral RNA copy number was also observed in HSAEC, especially when Larifan was added before infection (p = 0.0218). Larifan markedly reduced virus numbers in infected hamsters' lungs post-infection, with a more pronounced effect after intranasal administration (p = 0.0032). The administration of Larifan also reduced the amount of infections virus titer in the lungs (p = 0.0039). Improvements in the infection-induced pathological lesion severity in the lungs of animals treated with Larifan were also demonstrated. The inhibition of SARS-CoV-2 replication in vitro and the reduction in the viral load in the lungs of infected hamsters treated with Larifan alongside the improved lung histopathology suggests a potential use of Larifan in also controlling the COVID-19 disease in humans.